Using smart tags for simplified processing of proteins and peptides - Leong, Susanna Su Jan. (2009)
The main objectives of this work were to study and exploit the use of stimuli-responsive tags for purification, refolding and process intensification applications at an early stage of downstream processing. Results from this work have opened the way to overcome low purification efficiency and recoveries in bioprocessing flowsheets by elucidation of the means of polymer-biomolecule interaction for selective purification of cellular-derived contaminants, and protein refolding enhancement. Polyethyleneimine (PEI) and poly(methyl methacrylate) (Eudragit) were investigated for protein purification applications. PEI was superior to Eudragit for selective purification of cellular-derived nucleic acids, due to higher cationic properties compared to Eudragit. Polyethylene glycol (PEG) was investigated for its ‘refolding enhancing’ ability for lysozyme and bovine serum albumin model proteins. The effectiveness of PEG in improving refolding yields was dependent on PEG molecular weights and polymer to protein load ratios, where below the critical polymer to protein load, preferential binding of the polymer to the protein was dominant over self-association of the polymer molecules, thus minimising hydrophobic protein aggregation. Investigations of Eudragit as a refolding enhancer are currently ongoing. Preliminary results show that Eudragit can significantly enhance lysozyme refolding yield at optimum polymer and urea concentrations. It is envisaged that the ability of the pH-responsive polymer to first preferentially bind refolding intermediates to minimize hydrophobic-driven aggregation and then selectively extract the refolded protein into a purified phase upon a switch in pH conditions, will significantly advance current bioprocessing practices in both laboratory and industry settings.